Gut microbiota dependent anti-tumor immunity restricts melanoma growth in Rnf5 −/− mice - Yan Li (Nature Portfolio, 2019)
RNF5 is a ubiquitin ligase regulating ER stress response. Here the authors show that Rnf5 deficiency potentiates immune response against melanoma via altered microbiota, and isolate bacterial strains that confer the same phenotype to wild type mice.